Discussing sexual and relationship health with young people in a children's hospital: evaluation of a computer‐based resource. Issue 23 (2nd July 2013) - Bray, Lucy; Sanders, Caroline; McKenna, Jacqueline
Abstract : Aims and objectives: To investigate health professionals' evaluation of a computer‐based resource designed to improve discussions about sexual and relationship health with young people. Background: Evidence suggests that some health professionals can experience discomfort discussing sexual health and relationship issues with young people. Professionals within hospital settings should have the knowledge, competencies and skills to be able to ask young people sexual health questions and provide accurate sexual health education. Despite some educational material being available for community and adult services, there are no resources available, which are directly relevant to holding opportunistic discussions with young people within an acute children's hospital. Design: A descriptive survey design. Methods: One hundred and fourteen health professionals from a children's hospital in the UK were involved in evaluating a computer‐based resource. All completed an online questionnaire survey comprising of closed and open questions. Results: The health professionals reported that the computer‐based resource had a positive influence on their knowledge and clinical practice. The videos as well as the concise nature of the resource were evaluated highly. Learning was facilitated by professionals being able to control their learning through rerunning and accessing the resource on numerous occasions. Conclusions: An engaging, accessible computer‐based resource has the capability to positively impact on health professionals' knowledge of, and skills in, starting and holding sexual health conversations with young people accessing a children's hospital. Relevance to clinical practice: Health professionals working with children and young people value accessible, relevant and short computer‐based training. This can facilitate knowledge and skill acquisition despite variation in working patterns. Improving the knowledge and skills of professionals working with young people to facilitate appropriate yet opportunistic sexual health discussions is important within the public health agenda.